Growth of Surface Oxide Layers on Dendritic Cu Particles by Wet Treatment and Enhancement of Sinter-Bondability by Using Cu Paste Containing the Particles - Horyun Kim; Jong-Hyun Lee (Metals)
Pastes were prepared using dendritic Cu particles as fillers, and a compression die attachment process was implemented to establish a pure Cu joint using low-cost materials and high-speed sinter bonding. We aimed to grow an oxidation layer on the particle surface to improve sinter-bondability. Because the growth of the oxidation layer by general thermal oxidation methods makes it difficult to use as a filler owing to agglomeration between particles, we induced oxidation growth by wet surface treatment. Consequently, when the oxidation layer was appropriately grown by surface treatment using an acetic acid–ethanol solution, we obtained an improved joint strength, approximately 2.8 times higher than the existing excellent result based on a bonding time of 10 s. The joint formed in just 10 s at 300 °C in the air under 10 MPa compression showed a shear strength of 28.4 MPa. When the bonding time was increased to 60 s, the joint exhibited a higher strength (35.1 MPa) and a very dense microstructure without voids. These results were attributed to the acceleration of sintering by the in situ formation of more Cu nanoparticles, which effectively reduced the increased oxide layers in the particles using a reducing solvent.